Manajemen Konflik dalam Organisasi Industri : Studi Reflektif Berdasarkan Pengalaman Project Manager PT Petrosea - Fitri Fallah Prambudini; Wulan Seruni; Siti Maemunah; Muhammad Nur Julianto; Raniasari Bimanthi Esthi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Conflict management is an unavoidable challenge in complex and multicultural industrial environments, particularly when involving cross-functional teams with diverse backgrounds and expertise. This study aims to explore the sources of conflict, resolution strategies, and their impact on team performance in industrial organizations. Special emphasis is placed on the managerial competencies of a Project Manager in navigating the dynamics of a technical team. A reflective qualitative approach was employed, utilizing semi-structured interviews with an experienced Project Engineering Manager in the industrial sector. Thematic analysis was conducted to identify patterns of conflict, management strategies, and their influence on project outcomes. The findings indicate that the effectiveness of conflict management is largely determined by the leader’s ability to foster open communication and empathy within the team. A humanistic and constructive leadership style was found to minimize the negative impacts of conflict, while a confrontational approach tended to diminish motivation and performance. The practical implications of this study underscore the importance of enhancing leadership capacity and managerial communication to develop adaptive and collaborative project teams.